Pengembangan Media Video Pembelajaran Pembuatan Pola Jas di Kelas XI Tata Busana SMK Negeri 2 Jombang - Nuryani Charismawati; Indarti Indarti; Ma’rifatun Nashikhah; Imami Arum Tri Rahayu (Departement of Mathematics Education, 2024)
Learning video media is an illustration created by a computer with interactive visualization and audio, which also presents information, explains processes, explains complex concepts, teaches skills, and saves time and space. This development research aims to: 1) Describe the feasibility of learning videos for making jacket patterns in class XI Fashion Design at SMK Negeri 2 Jombang and 2) Describe the learning outcomes of class suit. The type of research used is research and development Research and Development (R&D) with the ADDIE model approach which includes analysis, design, development, implementation and evaluation stages. Product validation is carried out by experts in the field, namely lecturers and subject teachers. The trial was carried out on 34 students in class XI Fashion Design. The data collection instruments in this research used validation questionnaire sheets to measure the feasibility of learning videos as well as knowledge test sheets and product assessments to measure student learning outcomes. Descriptive data analysis techniques were used in this research to process and analyze the results of video validation questionnaires and student assessment sheets. The results of the research show that: 1) Produces a learning video media product for making jacket patterns and has been validated with a validity of 3.48 in the very good category and is worth trying out, 2) Obtaining student learning outcomes after applying the learning video media for making jacket patterns shows classical mastery of 97% in the very good category.